The Importance of Evaluation of Christian Religious Education Learning In The Era of Globalization - Nainggolan, Jaya; Sigalingging, Sery (Indo Green Journal, 2024)
Learning evaluation is an integral part of the educational process in schools, including Christian Religious Education (PAK) subjects. In the era of globalization that continues to grow, the importance of evaluating PAK learning is becoming increasingly prominent. Globalization indicates changes and developments in the world towards a more advanced direction. Therefore, evaluation of PAK learning must always be carried out to follow the dynamics of current developments so that learning objectives can be achieved in accordance with the current of globalization. This article discusses the steps and procedures for conducting a literature review on research entitled "The Importance of Evaluation of Christian Religious Education Learning in the Era of Globalization". These steps include determining the research focus, identifying keywords, literature search, literature selection, literature analysis, literature synthesis, writing a literature review, as well as revision and improvement. By conducting a systematic and comprehensive literature review, it is hoped that understanding of the importance of evaluating PAK learning in the era of globalization can be more detailed and measurable.